Tratamento de efluentes da indústria de celulose e papel com fungo filamentoso lignocelulósico - Santos, Alessandra Zacarias dos (1997)
The ligninolitic fungus Pleurotus ostreatoroseus was used to treat the E1 efluent of the first alcaline extraction of the kraf pulp bleaching stage. The fungus was used peletized in experiments under batch and continuous system, and in suspension in experiments under batch system. The experiments with the peletized fungus, under batch system, was accomplished by changing fungus quantity, initial pH adjustment, enzimatic induction and agitation, verifying the influence of this parameters on pH variation and reduction of color ant total phenols contents. In this experiments, the greatest quantity of fungus improved the decolorization, while agitation and initial pH adjustment afected it negatively. The initial pH adjustment influenced positively the total phenols removal. The enzimatic induction used don't improved fungus activity. The best decolorization result, about 61,2%, was obtained with 10% of fungus and without agitation and initial pH adjustment, after 120h. pH after this period reached 5,5. The maximun total phenols removal, 99.9%, was obtained, after 96h, with inoculation of 10% of fungus, without agitation and induction, and initial pH equal to 6,88. The final pH was 5,5. The performance of the peletized fungus, under continuous system, was studied by using a two liters turbulent flow bioreactor. Two experiments were realized. In the first one, the bioreactor operated with 4- day hydraulic retention time, and in the second one, with two and then with four days of hydraulic retention time. In the first experiment, the avarage removal of color and total phenols was 18,6 and 18,3%, respectively, after the addition of glucose. This indicated the need of na extra carbon source for the fungal treatment. In the second experiment, realized with the adition of several quantities of glucose, the maximum removal of color, total phenols and lignin/chlorolignin was 43,75, 23,08 e 29,4%. This confirmed the need of the glucose adition for continuous treatments of the E1 effluent with Pleurotus ostreatoroseus. The experiments with the fungus in suspension, was realized in the same conditions of the peletized fungus experiments, without indução. Agitaiton and initial pH adjustment don't influenced the results, while the greatest fungus quantity influenced them positively. 89% of decolorization, 87% of total phenols removal and 78% of lignin/chlorolignin removal was obtained at pH 3,9, after 120h of experiment. In this experiment the batch reactor was inoculated with 20% of fungus and operated with agitation, initial pH adjustment of 6,7 and without induction. The results indicate the potential for application of Pleurotus ostreatoroseus in the treatment of E1 effluente. This treatment, nevertheless, was more efficient when the fungus was used in suspension.